How do you differentiate #y=(e^(5x^4))/(e^(4x^2+3))#?

Answer 1

Rewrite as #y = e^(5x^4-4x^2-3)#, then use #d/dx(e^u) = e^u (du)/dx#

An important property of exponents is #a^n/a^m = a^(n-m)#
#y = e^(5x^4)/e^(4x^2+3) = e^(5x^4-4x^2-3)#
#y' = e^(5x^4-4x^2-3) * d/dx(5x^4-4x^2-3)#
# = (20x^3-8x)e^(5x^4-4x^2-3)#
Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 2

To differentiate the function y=(e^(5x^4))/(e^(4x^2+3)), you can use the quotient rule of differentiation:

Let u = e^(5x^4) and v = e^(4x^2+3).

Then, y' = (u'v - uv') / v^2, where u' and v' are the derivatives of u and v with respect to x.

First, find the derivatives: u' = d(e^(5x^4))/dx = 20x^3 * e^(5x^4) v' = d(e^(4x^2+3))/dx = 8x * e^(4x^2+3)

Now substitute into the quotient rule formula: y' = (20x^3 * e^(5x^4) * e^(4x^2+3) - e^(5x^4) * 8x * e^(4x^2+3)) / (e^(4x^2+3))^2

Simplify: y' = (20x^3 * e^(9x^4+3) - 8x * e^(9x^4+3)) / e^(8x^2+6)

Factor out common terms: y' = (e^(9x^4+3) * (20x^3 - 8x)) / e^(8x^2+6)

Simplify further: y' = (20x^3 - 8x) * e^(9x^4+3 - 8x^2 - 6)

Finally: y' = (20x^3 - 8x) * e^(9x^4-8x^2-3)

That's the derivative of the function y=(e^(5x^4))/(e^(4x^2+3)).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer 3

To differentiate the function ( y = \frac{e^{5x^4}}{e^{4x^2 + 3}} ), you can use the quotient rule.

The quotient rule states that if you have a function of the form ( \frac{u(x)}{v(x)} ), then its derivative is given by:

[ \frac{d}{dx} \left( \frac{u(x)}{v(x)} \right) = \frac{u'(x)v(x) - u(x)v'(x)}{(v(x))^2} ]

Applying this rule to the given function, where ( u(x) = e^{5x^4} ) and ( v(x) = e^{4x^2 + 3} ), and using the chain rule for differentiation, we have:

[ y' = \frac{(e^{5x^4})'(e^{4x^2 + 3}) - e^{5x^4}(e^{4x^2 + 3})'}{(e^{4x^2 + 3})^2} ]

[ = \frac{(5x^4)'e^{4x^2 + 3} - e^{5x^4}(8x)e^{4x^2 + 3}}{(e^{4x^2 + 3})^2} ]

[ = \frac{20x^3e^{4x^2 + 3} - 8xe^{9x^4 + 3}}{e^{2(4x^2 + 3)}} ]

[ = \frac{20x^3e^{4x^2 + 3} - 8xe^{4x^2 + 3}}{e^{8x^2 + 6}} ]

[ = \frac{4x^3(5 - 2x)e^{4x^2 + 3}}{e^{8x^2 + 6}} ]

So, the derivative of ( y ) with respect to ( x ) is ( y' = \frac{4x^3(5 - 2x)e^{4x^2 + 3}}{e^{8x^2 + 6}} ).

Sign up to view the whole answer

By signing up, you agree to our Terms of Service and Privacy Policy

Sign up with email
Answer from HIX Tutor

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

Not the question you need?

Drag image here or click to upload

Or press Ctrl + V to paste
Answer Background
HIX Tutor
Solve ANY homework problem with a smart AI
  • 98% accuracy study help
  • Covers math, physics, chemistry, biology, and more
  • Step-by-step, in-depth guides
  • Readily available 24/7